A Review of the Targeting System in Georgia : Proposed Reform Options - World Bank (World Bank, Washington, DC, 2020)
This paper first reviews the performance of the current targeting system and recommends improvements to the existing PMT formula. One implementation issue we identified is the inconsistency in how monetary and nonmonetary values are treated when calculating the PMT score. The practice has been to calculate the score based on monetary variables (income, social benefits package, and utility expenditures) at current nominal prices, which have inevitably inflated the predicted consumption. As the PMT formula was estimated at 2013 prices, the recommendation to correctly implement the current PMT formula would be to deflate all monetary variables to 2013 prices. Second, to further improve the poverty targeting accuracy, the paper presents the updated PMT model estimation and discusses the benefits and cost of transitioning to the new PMT formula. The empirical analysis is based on the 2018 HIES collected by the National Statistics Office of Georgia (Geostat), the latest available to the team at the time of the analysis. The remainder of this note is organized as follows. Section two looks at the performance of the current PMT model to identify key areas of possible improvements. Section three develops alternative estimates and proposes a new PMT formula, comparing its theoretical performance with that of the current one. This is followed by a discussion of the implementation of the formula in the following years to avoid problems encountered with the current approach. Section four goes further to make a more radical proposal to consider moving to an ‘hybrid’ approach combining an income test with the PMT, highlighting the advantages of the approach and the steps needed for its development and implementation. A final section provides a summary of key recommendations for the immediate, short, and medium term.